Conceptualizing Ancient Skepticism as a Global Pattern: Zhuangzi, Sextus Empiricus and Nāgārjuna - Lossau, Tammo (International journal for the study of skepticism, 2025)
Chinese, European and Indian ancient philosophy all saw movements of skepticism. However, the philosophical proximity in which these three movements stand is often not appreciated. In this article, I provide a comparison of the three most important figures of these movements: Zhuangzi, Sextus Empiricus and Nāgārjuna. I show a broad range of similarities with respect to the arguments they provide for their skeptical views, but also with respect to the way they conceptualize skepticism. I argue that in light of these similarities, we should regard ancient skepticism as a global phenomenon, rather than one confined to one tradition. I also argue that while there are differences in tonality, Zhuangzi and Nāgārjuna are properly classified as skeptics, contrary to their treatment by Matthew Bagger.